If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 7 = 6x + 7 Reorder the terms: 7 + 3x = 6x + 7 Reorder the terms: 7 + 3x = 7 + 6x Add '-7' to each side of the equation. 7 + -7 + 3x = 7 + -7 + 6x Combine like terms: 7 + -7 = 0 0 + 3x = 7 + -7 + 6x 3x = 7 + -7 + 6x Combine like terms: 7 + -7 = 0 3x = 0 + 6x 3x = 6x Solving 3x = 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 3x + -6x = 6x + -6x Combine like terms: 3x + -6x = -3x -3x = 6x + -6x Combine like terms: 6x + -6x = 0 -3x = 0 Divide each side by '-3'. x = 0 Simplifying x = 0
| 4(n-3)-2(-3+n)= | | -3(-5u+6)-3u=4(u-6)-8 | | 10+4y= | | 8(4x-1)-12x=(2x-6) | | n(2)+14=98 | | n(2)14=98 | | -1/2x+3(0)=-3 | | 2log(2x)=1 | | -6=3-m | | 125n^2-45=0 | | 0.04x+0.03(x-20)=1.25 | | 6x-61=-3x+65 | | 4(w+1)+4=20 | | 5x-3=6x-7 | | -3e+2=5e-4 | | 3-.75x=8 | | 8b^2+10b+3=0 | | 7x-10=-2-x | | f(25)+f(26)= | | -150+9x=122-8x | | 3(r-8)-(-4)=7 | | 6-4x=5x-12 | | 2(c+3)=-9 | | 4r^3+11r^2-3r=0 | | 2(m-7)=4 | | -47-11x=-3x+73 | | 8x+3+2x+17=180 | | 14x-32=24 | | 5-.666x=1 | | 0.2x+0.3=-0.5 | | -6-20=2n+4(1-3n) | | y=7.50x+25 |